2020
DOI: 10.1109/access.2020.2995461
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Optimal Battery Sizing Procedure Based on MG Frequency Security Criterion Using Coordinated Application of BESS, LED Lighting Loads, and Photovoltaic Systems

Abstract: This paper proposes a novel and optimal battery sizing procedure for the primary frequency control (PFC) of islanded microgrid (MG). The Battery Energy Storage System (BESS), Photovoltaic (PV) systems and LED Lighting Loads (LEDLLs) are coordinated to quickly intercept frequency deviation in the stage of PFC. The PVs decrease their power generation in the case of surplus of power generation. The LEDLLs decrease their power consumption in the case of power shortage. The BESS participates in PFC in both cases by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 33 publications
(75 reference statements)
0
39
0
Order By: Relevance
“…7 shows the MG network under study, which consists of a 0.4 kV distribution feeder connected to a 20 kV distribution network through a transformer. The network is the CIGRE distribution test system [4]. The MG contains a Solid-Oxide Fuel Cell (SOFC), a Microturbine (MT), a Diesel Generator (DEG), an ESS and two PV systems.…”
Section: Simulation Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…7 shows the MG network under study, which consists of a 0.4 kV distribution feeder connected to a 20 kV distribution network through a transformer. The network is the CIGRE distribution test system [4]. The MG contains a Solid-Oxide Fuel Cell (SOFC), a Microturbine (MT), a Diesel Generator (DEG), an ESS and two PV systems.…”
Section: Simulation Studiesmentioning
confidence: 99%
“…Based on statistical data of [4], the most severe contingency that the MG may experiences is 20 kW power shortage after an unplanned islanding. The SOFC and MT model for frequency regulation studies can be found in [39] while the DEG model is adopted from model which is presented in [40].…”
Section: B Simulation Studies For Frequency Regulation Of Islanded Mgmentioning
confidence: 99%
See 3 more Smart Citations